Tactics of the treatment of left atrial angiosarcoma - R.M. Vitovskyi; V.V. Isaіenko; D.М. Dyadyun; O.A. Pishchurin; V.F. Onishchenko; Ya.R. Ivanov; O.V. Kupchinskyi (Кардіохірургія та інтервенційна кардіологія)
The aim – to characterize the difficulties of diagnosis, the choice of tactics and the application of a new approach to the surgical treatment of malignant neoplasms, aimed at reducing the likelihood of recurrent intracardiac tumor growth. Materials and methods. The article presents a case of observation of a malignant tumor of the left atrium (LA) – angiosarcoma – in a patient aged 41 years, hospitalized with a previously established diagnosis of stage II lung sarcoidosis and myxoma of the LA. Results. Taking into account the severe obstruction of the mitral valve by the neoplasm, a decision was made on emergency surgical treatment. Neoplasm was visualized in the LA cavity, filling almost its entire cavity. A tumor 12 × 7 × 5 cm was removed. Histological examination of the tumor revealed a low-grade angiofibrosarcoma. Two weeks after discharge, computed tomography revealed atrial tumor recurrence. Given the observed fast recurrence, it was decided to separate the tumor tissue from the lumen of the LA and to avoid direct contact with blood. Therefore, the mouth of the right lower pulmonary vein was closed with a patch from the autopericardium. The control CT studies after a course of chemotherapy recorded moderate tumor growth in the projection of the lung tissue; there was no recurrent tumor growth in the cavity of the LA. Conclusions. Surgical treatment of malignant heart tumors should be aimed at the most radical removal of the neoplasm, the restoration of adequate intracardiac hemodynamics, and in cases of the impossibility of performing a radical operation, at isolating the tumor tissue from direct contact with the blood to prevent rapid recurrent intracardiac growth of the neoplasm.